Fully Polymeric Domes as High-Stroke Biasing System for Soft Dielectric Elastomer Actuators - Neu, Julian; Hubertus, Jonas; Croce, Sipontina; Schultes, Günter; Seelecke, Stefan; Rizzello, Gianluca (Frontiers in Robotics and AI, 2021)
The availability of compliant actuators is essential for the development of soft robotic systems. Dielectric elastomers (DEs) represent a class of smart actuators which has gained a significant popularity in soft robotics, due to their unique mix of large deformation, lightweight, fast response, and low cost. A DE consists of a thin elastomer membrane coated with flexible electrodes on both sides.When a high voltage is applied to the electrodes, the membrane undergoes a controllable mechanical deformation.In order to produce a significant actuation stroke, a DE membrane must be coupled with a mechanical biasing system. Commonly used spring-like bias elements, however, are generally made of rigid materials such as steel, and thus they do not meet the compliance requirements of soft robotic applications.To overcome this issue, in this paper we propose a novel type of compliant mechanism as biasing elements for DE actuators, namely a three-dimensional polymeric dome. When properly designed, such types of mechanisms exhibit a region of negative stiffness in their force-displacement behavior. This feature, in combination with the intrinsic softness of the polymeric material, ensures large actuation strokes as well as compliance compatibility with soft robots.After presenting the novel biasing concept, the overall soft actuator design, manufacturing, and assembly are discussed. Finally, experimental characterization is conducted, and the suitability for soft robotic applications is assessed.